(untitled) (International Seven Journal of Multidisciplinary, 2024)
The prevalence of congenital heart diseases, especially ventricular septal defect, and its relationship with pulmonary hypertension highlight the need for an integrated approach and early interventions to improve clinical outcomes and quality of life of patients. These conditions, which represent a significant challenge for neonatal public health, require both identification and appropriate management to prevent serious complications. The objective of this study was to analyze the relationship between the various types of congenital heart disease and the risk of developing pulmonary hypertension. For this, a bibliographic search was adopted as a procedure, searching for and selecting scientific studies published between the years 2020 and 2024 in the SciELO and LILACS databases. The inclusion criteria included studies that discussed the chronic use of benzodiazepines and its relationship with other substance use disorders, while the exclusion criteria eliminated publications without empirical data or focused on specific samples. Through the analysis of the results, as a conclusion, it was found that the relationship between congenital heart diseases and pulmonary hypertension is strongly influenced by the type and severity of cardiac anomalies, and early diagnosis and personalization of interventions are essential to improve the prognosis and quality of life of patients.